Mechanisms of Action of Mesenchymal Stem Cells in Metabolic-Associated Fatty Liver Disease - Sitong Yi; Qingwei Cong; Ying Zhu; Qiumin Xu (Stem Cells International)
Metabolic-associated fatty liver disease (MAFLD) is currently the most common chronic liver disease worldwide. However, its pathophysiological mechanism is complicated, and currently, it has no FDA-approved pharmacological therapies. In recent years, mesenchymal stem cell (MSC) therapy has attracted increasing attention in the treatment of hepatic diseases. MSCs are multipotent stromal cells that originated from mesoderm mesenchyme, which have self-renewal and multipotent differentiation capability. Recent experiments and studies have found that MSCs have the latent capacity to be used for MAFLD treatment. MSCs have the potential to differentiate into hepatocytes, which could be induced into hepatocyte-like cells (HLCs) with liver-specific morphology and function under appropriate conditions to promote liver tissue regeneration. They can also reduce liver tissue injury and reverse the development of MAFLD by regulating immune response, antifibrotic activities, and lipid metabolism. Moreover, several advantages are attributed to MSC-derived exosomes (MSC-exosomes), such as targeted delivery, reliable reparability, and poor immunogenicity. After entering the target cells, MSC-exosomes help regulate cell function and signal transduction; thus, it is expected to become an emerging treatment for MAFLD. In this review, we comprehensively discussed the roles of MSCs in MAFLD, main signaling pathways of MSCs that affect MAFLD, and mechanisms of MSC-exosomes on MAFLD.